Analysis of communication media in emergency warning visuals; Indonesia Regional Election Bill: Theory and Understanding - Rina Megasari Panjaitan (Jurnal Indonesia Sosial Teknologi, 2024)
This study examines the role of communication media, particularly in the dissemination of emergency content with a blue Garuda backdrop related to the Regional Election Bill (RUU Pilkada) in Indonesia. The primary focus of this research is to understand how communication, especially through social media, is utilized to mobilize users and generate public opinion communication. Using a qualitative approach, the study analyzes visual demonstration content spread through social media and applies theories of human communication and mediated communication to user perception and political engagement. The findings indicate that social media has become an extremely effective political communication tool, allowing information to spread rapidly and reach a broad audience. Emergency warning visuals shared on social media platforms are effective in capturing public attention, triggering mass mobilization, and stimulating political discussions across different segments of society. The study concludes that social media plays a crucial role in shaping public opinion and encouraging political participation concerning legislative issues such as the RUU Pilkada. The results highlight the importance of understanding communication from media communication perspectives for maintaining healthy and productive communication practices.